Effects of high‐fat diet‐induced adipokines and cytokines on colorectal cancer development - Jian Zhang; Shikui Guo; Jinyuan Li; Weimin Bao; Peng Zhang; Yingguang Huang; Ping Ling; Yongzhi Wang; Quan Zhao (FEBS Open Bio, 2019)
Colorectal cancer (CRC) is the third most common tumor worldwide, and recent epidemiological studies have indicated that obesity contributes to the morbidity and mortality of CRC. Furthermore, obesity‐related adipokines have been shown to be closely related to the incidence of CRC, but the underlying mechanisms are unclear. Here, we investigated the effects of high‐fat diet‐induced adipokines and cytokines on the development of CRC in vitro and in vivo. For the in vivo assays, we divided 2‐week‐old C57BL/6J‐ApcMin/J male mice into three groups: normal‐fat diet (ND), high‐fat and high‐sugar feed (HFHS), and high‐fat and low‐sugar feed (HFLS). After 1 week, all mice were injected with 20 mg·kg−1 1,2‐dimethylhydrazine once weekly for 10 consecutive weeks. Body weight, liver weight, epididymal fat weight and blood glucose levels were greatly increased in HFHS and HFLS groups compared with the ND group, and the expression levels of some adipokines and cytokines were obviously higher in HFHS or HFLS mice compared with ND mice. For the in vitro assays, HCT116 CRC cells were treated with sera of ND, HFHS or HFLS groups, or serum‐free media as a negative control. We observed that sera derived from HFHS or HFLS mice that contain excess adipokines and cytokines promoted the proliferation, migration and invasion of HCT116 cells compared with the ND sera‐conditioned medium or serum‐free medium group. Therefore, high‐fat diet‐induced adipokines and cytokines may promote the progression of CRC in vivo and in vitro.